Government Policy Strategy towards Empowering MSMEs in the Covid-19 Pandemic at the Bulak Fish Market Center, Surabaya City - Rumanintya Putri; Muhammad Chasan Amrulloh; Joko Sutrisno; S Saptana; Nufera Lupika Dani (CV. Media Digital Publikasi Indonesia, 2023)
The Covid-19 pandemic has greatly impacted the economy of MSMEs, and implementing economic recovery strategies is essential in mitigating its effects. Economic recovery efforts should focus on improving welfare measures for people and nations, leading to international economic recovery. Starting at the micro level and moving up to the macro level is crucial in ensuring that the recovery efforts benefit all levels of the economy. The Bulak Fish Market Center is a vital hub for MSMEs dealing with fish and other natural resources, sourced from the sea. The pandemic has led to reduced jobs, production, and income for MSMEs, underscoring the need for effective government policies to support their growth and development. This study seeks to examine the impact of government policies aimed at empowering MSMEs and fostering business development strategies, particularly in the digitalization era, at the Bulak Market Center in Surabaya City. Business development aspects such as digital marketing, product and service quality assurance, and customer relationship marketing were analyzed using qualitative research methods such as observations, interviews, documentation, and analysis of previous studies. The results indicate that government policies intended to support economic recovery through MSMEs are not fully implemented at the Bulak Fish Market Center. The research findings can provide valuable insights to the government to evaluate the effectiveness of their policies and educate readers who are pursuing similar businesses. However, it should be noted that the research only focused on one object, and further research is necessary to generalize the findings to a wider population